2012
DOI: 10.1002/casp.2136
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Risk Factors for Cyberbullying in Adolescence

Abstract: Cyberbullying has emerged as a new form of antisocial behaviour in the context of online communication over the last decade. The present study investigates potential longitudinal risk factors for cyberbullying. A total of 835 Swiss seventh graders participated in a short-term longitudinal study (two assessments 6 months apart). Students reported on the frequency of cyberbullying, traditional bullying, rule-breaking behaviour, cybervictimisation, traditional victimisation, and frequency of online communication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
132
1
22

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(168 citation statements)
references
References 45 publications
13
132
1
22
Order By: Relevance
“…Our findings showed that higher bullying scores were associated with higher moral deficiencies scores in the cross-sectional view, which is consistent with results from previous cross-sectional research (Hymel et al, 2005;Menesini et al, 2003;F Sticca, Ruggieri, Alsaker, & Perren, 2012). In the longitudinal analyses, we were able to show that the initial levels of moral deficiencies predicted the development of bullying, while the contrary was not the case (i.e., initial levels of involvement in bullying are not associated with changes in moral deficiencies).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings showed that higher bullying scores were associated with higher moral deficiencies scores in the cross-sectional view, which is consistent with results from previous cross-sectional research (Hymel et al, 2005;Menesini et al, 2003;F Sticca, Ruggieri, Alsaker, & Perren, 2012). In the longitudinal analyses, we were able to show that the initial levels of moral deficiencies predicted the development of bullying, while the contrary was not the case (i.e., initial levels of involvement in bullying are not associated with changes in moral deficiencies).…”
Section: Discussionsupporting
confidence: 93%
“…other studies found no association between moral disengagement and cyberbullying once moral values and feelings of remorse or traditional bullying and rule-breaking behaviors (Sticca, Ruggieri, Alsaker, & Perren, 2013) were taken into account. Therefore, evidence for the association between moral cognitions and traditional bullying is stronger than evidence for its association with cyberbullying.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…In fact, some researchers have shown that when the extent of Internet use and cyberbullying victimization is taken into consideration, their relationships with cyberbullying perpetration might not be as clear as proposed by other studies. For example, Sticca, Ruggieri, Alsaker, and Perren (2013) found that, while the extent of Internet usage was a significant longitudinal risk factor for cyberbullying perpetration, cyberbullying victimization was not. The two variables, therefore, might not be contributing to the risk for one's involvement in cyberbullying perpetration in a purely additive manner.…”
Section: From a Variable-oriented To A Personoriented Approach To Cybmentioning
confidence: 99%
“…Auch in der Schweiz hat Mobbing eine hohe Prävalenz. Sticca und Kollegen befragten 835 Jugendliche im Alter von zwölf bis fünfzehn Jahren hinsichtlich der Bedeutung alter und neuer Mobbingformen wie digitales und Cybermobbing im Schulalltag (Sticca, Ruggieri, Alsaker, Perren, 2013 Prüfungsangst ist eine Angst, die sich auf die Bewertung der eigenen Leistungsfä-higkeit bezieht. Prüfungsangst wird im DSM-IV (APA, 2000) als Soziale Phobie klassifiziert und tritt häufig zusammen mit anderen sozialen Ängsten auf.…”
Section: Hintergrundunclassified